Effectiveness of dual-task computerized cognitive training in the prevention of postoperative cognitive dysfunction in coronary bypass surgery - O. A. Trubnikova; I. V. Tarasova; I. N. Kukhareva; T. B. Temnikova; A. S. Sosnina; I. D. Syrova; D. S. Kupriyanova; O. I. Barbarash (Кардиоваскулярная терапия и профилактика)
Aim. To evaluate the effectiveness of dual-task computerized cognitive training (CCT) in the prevention of postoperative cognitive dysfunction in patients after on-pump coronary artery bypass grafting (CABG).Material and methods. This cohort prospective study included 68 patients (median age, 64 years [54; 69]) admitted for elective on-pump CABG. In addition to the standard preoperative examination, all patients underwent advanced neuropsychological and neurophysiological examination. Starting from 3-4 days of the postoperative period, all patients underwent dual-task CCT.Results. After 8-10 days, early postoperative cognitive dysfunction was observed in 37 (54,4%) patients from CCT group, while in patients without training in 69,3% of cases (n=79). The best results of cognitive functioning were achieved in neurodynamics and short-term memory. In addition, in patients who completed the training course, a postoperative increase in the frontooccipital gradient of theta rhythm was observed.Conclusion. Neuropsychological and neurophysiological assessment have demonstrated the limited effectiveness of a short-term dual task CCT using in the prevention of early postoperative cognitive dysfunction in patients after on-pump CABG. The dual task method can be an additional preventive intervention in the development of a personalized approach to cognitive rehabilitation therapy in cardiac surgery patients.